Collaborative Innovation Mechanism of GBA in China A Free Port Approach - Ba, Shusong; Shen, Peng.; Liang, Xinning (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book aims to explore the development model of Great Bay Area (GBA) of China as economic engine under the context of open policy. Based on comprehensive research, both theoretically and practically, on the leading free ports in the world and the regional development of well-known bay areas, it analyzes the challenges and opportunities of GBA synergetic free ports. A series of initiatives on the development of GBA synergetic free ports are proposed, including the synergy of space, industry, finance, technological innovation, institution, social governance, and personnel. Also, it ends with a system dynamic model to simulate the regional impact on GBA synergetic free ports, which indicates that economic development, trade, government finance, and population agglomeration would be improved significantly, in the GBA synergetic free ports scenario.
Chapter 1. Background of GBA Synergetic Free ports -- Chapter 2. Theoretical Foundation of Free ports and Regional Synergetic Development -- Chapter 3. Best Practices of the Leading Free Ports of the World -- Chapter 4. Study on Regional Synergetic Development of Well-known Bay Areas -- Chapter 5. Challenges and Opportunities of GBA Synergetic Free ports -- Chapter 6. Panorama of GBA Synergetic Free ports -- Chapter 7. Simulation Analysis of the regional impact of GBA Synergetic Free ports -- Chapter 8. Summary and Future Studies. .
Keywords: Regional economics; Spatial economics; Shipping; Economic development; International trade; Regional and Spatial Economics; Maritime Economics; Economic Growth; International Trade